Volunteers in a hospital – opportunity or threat? Exploratory study from Finland. Issue 5 (2014) - ,; ,
Abstract : Purpose – Finland represents one of the Nordic welfare states where the role of the public sector as the organiser and provider of health and social care is strong. However, the amount of voluntary work in social and health care services is surprisingly big. The strongest advocates for keeping the volunteers outside are hospitals and health centres while at the same time they are suffering from shortages of staff and staff is reporting lack of time to provide needed care for their patients. The purpose of this paper is to report the results of a study of the attitudes of professionals towards voluntary work in hospitals.Design/methodology/approach – The paper is based on an exploratory study done in three hospitals, two from an urban area and one in a rural area. The interviewees represent nursing and care staff ( n =21). The main questions were how staff members see options, constraints and drawbacks of volunteering regarding professional roles, work division, coordination and management.Findings – Attitudes of staff varied from positive to conditional. The approaches towards voluntary work varied from holistic to task‐centred or patient‐centred and were linked with organisational approach, professional approach or considerations of patients' well‐being. Critical views were expressed related to managerial issues, patients' safety and quality of care. Increasing the amount of voluntary work done in hospitals would require a considered strategy and a specifically designed process for coordination, management and rules on the division of labour.Research limitations/implications – The research raised themes for further quantitative studies to elaborate the findings on the similarities and differences of the opinions of different staff categories and to be able to develop further the heuristic model of volunteer management triangle suggested in the paper.Social implications – The study raises questions of the need and promotion of volunteers in general and especially in health care services. It also raises critical views related to voluntary work in hospitals.Originality/value – The study is a new initiative to discuss voluntary work and how to manage volunteers in hospitals. It provides valuable knowledge for practitioners in health care involved in volunteer management and coordination. Acknowledgements : Jenni Malinen, RN, participated in the research by doing and transcribing several interviews.Professor Amanda Woodward from Michigan State University commented the text and proofread the drafts. The previous version of this paper was presented in the 8th International Critical Management Studies (CMS) Conference, 10‐12 July 2013, Manchester, UK. The authors thank the participants of the conference stream Critical Views on Health Care Management for their feedback.